2018
DOI: 10.1016/j.actatropica.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Using adult Aedes aegypti females to predict areas at risk for dengue transmission: A spatial case-control study

Abstract: Spatial analysis techniques and the number of adult Ae. aegypti females were used to produce an indicator of dengue risk. The index can be applied at various levels of spatial aggregation for an entire study area, as well as for sub-areas, such as city blocks. Even though the index is adequate to predict dengue risk, it should be tested and validated in various scenarios before routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…Moreover, the majority of those studies used immature Aedes indices to assess the infestation level (density) in the study area [ 61 , 62 ]. Nevertheless, a study in Sao Paulo, Brazil demonstrated a strong association between numbers of female Aedes collected over a fortnight and dengue incidence [ 89 ]. Their findings were obtained after the re-introduction of DENV serotype 3, to which the majority of the population were susceptible, thus facilitating the assessment of entomological risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the majority of those studies used immature Aedes indices to assess the infestation level (density) in the study area [ 61 , 62 ]. Nevertheless, a study in Sao Paulo, Brazil demonstrated a strong association between numbers of female Aedes collected over a fortnight and dengue incidence [ 89 ]. Their findings were obtained after the re-introduction of DENV serotype 3, to which the majority of the population were susceptible, thus facilitating the assessment of entomological risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of dengue transmission is influenced by various factors, including trade of goods and human mobility, population density, urbanization, climate, presence of invasive populations of Aedes vectors and pathogens, virus evolution, density of competent vectors, and ineffective vector control strategies ( 18 , 19 ). While an efficient vaccine is still under research, entomological surveillance and vector control remain the only ways to prevent and control dengue transmission ( 19 21 ). Therefore, WHO recommends a routine vector surveillance to provide a quantifiable measurement of dengue vector fluctuations and their geographical distribution for assessing the risk of outbreaks and to determine vector control interventions ( 2 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis is based on mapping the intrinsic growth rate observed for female Aedes mosquitoes. Recent research shows the adequacy and sometimes the superiority of female mosquito-based indices instead of egg and larvae-based measures to predict dengue risk ( Parra et al., 2018 ). Certainly the spatial and temporal ranges found in this work need to be considered carefully before any generalisation (unless as prior-information for future Bayesian framework).…”
Section: Discussionmentioning
confidence: 99%